Abnormalities of the DNA Methylation Mark and Its Machinery: An Emerging Cause of Neurologic Dysfunction - Weissman, Jacqueline; Naidu, Sakkubai; Bjornsson, Hans T. (Seminars in Neurology, 2014)
Recently, Mendelian disorders of the DNA methylation machinery have been described which demonstrate the complex roles of epigenetics in neurodevelopment and disease. For example, defects of DNMT1, the maintenance methyltransferase, lead to adult-onset progressive neurologic disorders, whereas defects of the de novo methyltransferases DNMT3A and DNMT3B lead to nonprogressive neurodevelopmental conditions. Furthermore, patients with DNMT3A deficiency demonstrate overgrowth, a feature common to disorders of histone machinery and imprinting disorders, highlighting the interconnectedness of the many epigenetic layers. Disorders of the DNA methylation machinery include both the aforementioned “writers” and also the “readers” of the methyl mark, such as MeCP2, the cause of Rett syndrome. Any dosage disruption, either haploinsufficiency or overexpression of DNA methylation machinery leads to widespread gene expression changes in trans, disrupting expression of a subset of target genes that contribute to individual disease phenotypes. In contrast, classical imprinting disorders such as Angelman syndrome have been thought generally to cause epigenetic dysregulation in cis. However, the recent description of multilocus methylation disorders challenges this generalization. Here, in addition to summarizing recent developments in identifying the pathogenesis of these diseases, we highlight clinical considerations and some unexpected therapeutic opportunities, such as topoisomerase inhibitors for classical imprinting disorders.
Keywords: intellectual disability; imprinting; Rett syndrome; Angelman syndrome